Temperament and dominance relate to feeding behaviour and activity in beef cattle: implications for performance and methane emissions. (2nd April 2018) - Llonch, P.; Somarriba, M.; Duthie, C. A.; Troy, S.; Roehe, R.; Rooke, J.; Haskell, M. J.; Turner, S. P.
Abstract : In beef cattle, feeding behaviour and activity are associated with feed efficiency and methane (CH4 ) emissions. This study aimed to understand the underlying traits responsible for the contribution of cattle behaviour to individual differences in feed efficiency, performance and CH4 emissions. A total of 84 steers (530±114 kg BW) of two different breeds (crossbreed Charolais and Luing) were used. The experiment was a 2×2×3 factorial design with breed, basal diets (concentrate v . mixed) and dietary treatments (no additive, calcium nitrate or rapeseed cake) as the main factors. The individual dry matter intake (DMI; kg) was recorded daily and the BW was measured weekly over a 56-day period. Ultrasound fat depth was measured on day 56. Based on the previous data, the indexes average daily gain, food conversion and residual feed intake (RFI) were calculated. The frequency of meals, the duration per visit and the time spent feeding per day were taken as feeding behaviour measures. Daily activity was measured using the number of steps, the number of standing bouts and the time standing per day. Agonistic interactions (including the number of contacts, aggressive interactions, and displacements per day) between steers at the feeders were assessed as indicators of dominance. Temperament was assessed using the crush score test (which measures restlessness when restrained) and the flight speed on release from restraint. Statistical analysis was performed using multivariate regression models. Steers that spent more time eating showed better feed efficiency ( P =0.039), which can be due to greater secretion of saliva. Feeding time was longer with the mixed diet ( P <0.001), Luings ( P =0.009) and dominant steers ( P =0.032). Higher activity (more steps) in the pen was associated with poorer RFI, possibly because of higher energy expenditure for muscle activity. Frequent meals contributed to a reduction in CH4 emissions per kg DMI. The meal frequency was higher with a mixed diet ( P <0.001) and increased in more temperamental ( P =0.003) and dominant ( P =0.017) steers. In addition, feed intake was lower ( P =0.032) in more temperamental steers. This study reveals that efficiency increases with a longer feeding time and CH4 emissions decrease with more frequent meals. As dominant steers eat more frequently and for longer, a reduction in competition at the feeder would improve both feed efficiency and CH4 emissions. Feed efficiency can also be improved through a reduction in activity. Selection for calmer cattle would reduce activity and increase feed intake, which may improve feed efficiency and promote growth, respectively.